Healthy cats tolerate long-term daily feeding of Cannabidiol - Coltherd, Jennifer C.; Bednall, Robyn; Bakke, Anne Marie; Ellerby, Zack; Newman, Christopher; Watson, Phillip; Logan, Darren W.; Holcombe, Lucy J. (Frontiers in Veterinary Science, 2024)
Cannabidiol (CBD)-containing products are widely commercially available for companion animals, mirroring popularity in human use. Although data on the safety and efficacy of longer-term oral supplementation is increasing in dogs, evidence remains lacking in cats. The purpose of these studies was to address gaps in the knowledge around the longer-term suitability and tolerance of a tetrahydrocannabinol (THC)-free CBD distillate in clinically healthy cats. The studies were randomised, blinded and placebo-controlled. The first study supplemented cats with either a placebo oil (n=10) or with 4mg/kg body weight (BW) CBD in placebo oil (n=9) daily, with a meal, for 4 weeks. The concentration of CBD in plasma was measured over 4 hours at d0 (first dose) and again at d14 (after 2 weeks of daily dosing). The second study supplemented cats daily with either placebo oil (n=10) or 4mg/kg BW CBD in placebo oil (n=10) for a period of 26 weeks. A comprehensive suite of physiological health measures were performed throughout the study at baseline (week 0) and after 4, 10, 18 and 26 weeks of feeding, followed by a 4 week washout sample (week 30). Postprandial plasma CBD time course data, at both d0 and d14, showed a peak plasma CBD concentration at 2 hours after the dose. This peak was 251 (95% CI: 108.7, 393.4) and 431 (95% CI: 288.7, 573.4) ng/mL CBD at d0 and d14 respectively, and area under the curve concentration was higher by 91.5 (95% CI:33.1, 149.9) ng-h/mL after 2 weeks of supplementation (p=0.002). While in the first study the CBD group displayed increased alanine aminotransferase (ALT; 68.7 (95% CI: 43.23, 109.2) U/L) at week 4 compared to the placebo control group (1.44-fold increase (95% CI: 0.813, 2.54)), statistical equivalence (at 2-fold limits) was found for ALT across the duration of the second, longer-term study. All other biochemistry and haematology data showed no clinically significant differences between supplement groups. Data presented here suggest that a THC-free, CBD distillate fed at a dose of 4mg/kg BW was absorbed into plasma and well tolerated by healthy cats when supplemented over a period of 26 weeks.